The New Westminster Dictionary of Liturgy and Worship - John Gordon Davies 1919-1990 (Philadelphia Westminster Press, 1986)
This newly revised one-volume reference book dramatically illustrates how worship can reflect changing times and yet remain a constant occasion for encounter with the living God.
1st American ed.
British ed. published under title: A New dictionary of liturgy & worship.
Revised edition of: The Westminster dictionary of worship. 1979, c1972.
Keywords: Liturgy (3GddGghJ GdWbSj (B- (3GddjJhQLjGs; Liturgics -- Dictionaries; Theology; Worship -- Dictionaries